2013
DOI: 10.1007/s13762-013-0306-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of adsorption potential of bamboo biochar for metal-complex dye: equilibrium, kinetics and artificial neural network modeling

Abstract: Metal-complex dyes are widely used in textile industry, but harmful to the environment and human health due to aromatic structure and heavy metal ions. The objective of this work was to evaluate the adsorption potential of bamboo biochar for the removal of metalcomplex dye acid black 172 from solutions. Freundlich model was more suitable for the adsorption process of bamboo biochar than Langmuir isotherm, indicating multilayer adsorption of acid black 172 on a heterogeneous bamboo biochar surface. Adsorption k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(44 citation statements)
references
References 33 publications
5
39
0
Order By: Relevance
“…The optimal structure of the neural network for sorption amount predictions was sought computing the measures of fit of simulation results to measurements (MAE, MAPE). That was done for a number of neurons in the hidden layer (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) adopted in the study and for linear, exponential (exp), sine (sin), sigmoidal (sigm) and hyperbolic tangent activation functions. In the output layer, linear activation function was assumed.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The optimal structure of the neural network for sorption amount predictions was sought computing the measures of fit of simulation results to measurements (MAE, MAPE). That was done for a number of neurons in the hidden layer (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) adopted in the study and for linear, exponential (exp), sine (sin), sigmoidal (sigm) and hyperbolic tangent activation functions. In the output layer, linear activation function was assumed.…”
Section: Methodsmentioning
confidence: 99%
“…It is a complex task that requires substantial labour input and generates high costs while the results obtained describe only one particular adsorbent -adsorbate system. However, both the literature on the subject [1][2][3][4][5][6][7][8][9][10][11][12] and technological practice provide databases of sorption results for activated carbon-adsorbate systems that have already been investigated. Therefore, it seems reasonable to make use of those data to predict sorption in the systems that show comparable properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al [57] studied adsorption isotherms at different initial of Cu (II) and Zn (II) that ranged from 0.1 to 5.0 mM that has proven that the Langmuir model (R 2 > 0.998) fit the data better than the Freundlich model (R 2 were 0.86-0.94). Many researchers also reported that adsorption of trace metals by biochar fits better to Freundlich than Langmuir isotherm in the dynamic data [26,131,132,133].…”
Section: Adsorption Isothermmentioning
confidence: 99%
“…The adsorption of methyl violet on -COO-and hydrophilic was dominant. Sun et al [37] respectively obtained biochar from anaerobic digestion residue, palm bark and tree, through pyrolysis at 400 C for 30 min, respectively. Under the condition of 40 C, pH 7, 4 mg/L methyl blue, the removal efficiency was 99.5, 99.3 and 86.1%, respectively.…”
Section: Organic Pollutantsmentioning
confidence: 99%